2019
DOI: 10.3201/eid2506.180392
|View full text |Cite
|
Sign up to set email alerts
|

Joint Estimation of Relative Risk for Dengue and Zika Infections, Colombia, 2015–2016

Abstract: We jointly estimated relative risk for dengue and Zika virus disease (Zika) in Colombia, establishing the spatial association between them at the department and city levels for October 2015–December 2016. Cases of dengue and Zika were allocated to the 87 municipalities of 1 department and the 293 census sections of 1 city in Colombia. We fitted 8 hierarchical Bayesian Poisson joint models of relative risk for dengue and Zika, including area- and disease-specific random effects accounting for several spatial pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Medellin had the highest proportion of “undifferentiated fevers” in the health care facility diagnosis that were later reported to SIVIGILA as either dengue, chikungunya, or Zika. Similarly, this could be associated with the low number of cases of chikungunya and Zika in Medellin, compared to the presence of these diseases in Cali and Villavicencio and the rest of the country [ 29 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Medellin had the highest proportion of “undifferentiated fevers” in the health care facility diagnosis that were later reported to SIVIGILA as either dengue, chikungunya, or Zika. Similarly, this could be associated with the low number of cases of chikungunya and Zika in Medellin, compared to the presence of these diseases in Cali and Villavicencio and the rest of the country [ 29 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported other associations, such as the presence and persistence of rheumatic pain and aging for CHIKV ( 30 ), and the possibility of death with DENV ( 29 , 31 ) and CHIKV ( 32 ) infections. Being a male child and an elderly man have been associated with DENV and CHIKV infections ( 33 , 34 ), but other studies have described an increased risk of CHIKV infection in older women ( 35 ) and increased risk of ZIKV and DENV infections in children of both sexes ( 36 , 37 ).…”
Section: Resultsmentioning
confidence: 99%
“…Rev Panam Salud Publica 47, 2023 | www.paho.org/journal | https://doi.org/10.26633/RPSP.2023. 34 CHIKV has reached several regions of Europe and Asia and it was reported for the first time in the Americas and the Caribbean in 2013. In 2015, almost 1 million cases were reported, which resulted in 7 126 deaths.…”
mentioning
confidence: 99%
“…Dengue notification in Colombia is mandatory and cases are individually registered in the national surveillance system (SIVIGILA), using the locally validated and standardized codes 210 and 220 for dengue and severe dengue, respectively (27). We chose to use this dataset given the availability and to avoid the potential threat of misclassification with other arboviruses when using data of notified cases from 2014 and onwards, when Chikungunya and zika were introduced in the country (13, 28).…”
Section: Methodsmentioning
confidence: 99%
“…Colombia is one of the Latin American countries with the highest burden of dengue (3, 4) and within Colombia, dengue burden concentrates geographically in 50 of the 778 municipalities that routinely report dengue cases (1, 2, 12, 13). Given the spatial heterogeneity of dengue distribution, including its concentration in low socioeconomic settings, and the limitations of current dengue control strategies (14-18), it is important to investigate the spatial distribution of dengue cases.…”
Section: Introductionmentioning
confidence: 99%